Public debt growth, great recession and fiscal consolidation-the Serbian episode - Andric, Vladimir; Minovic, Jelena (Serbian Journal of Management, 2018)
This paper analyses the dynamics of public debt growth in Serbia between the fourth quarter of 2004 (2004Q4) and the same quarter of 2017 (2017Q4). The empirical estimates capture the upward shift in public debt growth from the onset of the Great Recession. The results also show how policy makers have managed to curb the growth of public indebtedness in Serbia between 2014Q4-2017Q4. The government should, however, put greater fiscal efforts to reduce the overall share of public debt in gross domestic product in accordance with the fiscal rules of the Republic of Serbia and the Maastricht convergence criteria.